Cytologic-Histologic Correlation Practices for Nongynecologic Cytology Specimens: A Survey by the College of American Pathologists Cytopathology Committee. - Nguyen, Lananh N.; Crothers, Barbara A.; Souers, Rhona J.; Barkan, Güliz A.; Brainard, Jennifer; Nassar, Aziza; Rollins, Susan; Tabatabai, Z. Laura; Tabbara, Sana; Witt, Benjamin; Booth, Christine N. (Archives of Pathology & Laboratory Medicine, 2024)
Context.--: Cytologic-histologic correlation (CHC) is a Clinical Laboratory Improvement Amendments-mandated requirement for gynecologic cytology, but no similar requirement exists for nongynecologic cytology. This study presents the findings from a College of American Pathologists survey of nongynecologic cytology practice patterns. Objective.--: To survey the current CHC practices for nongynecologic cytology. Design.--: Data were analyzed from a survey developed by the committee and distributed to participants in the Nongynecologic Cytopathology Education Program mailing. Results.--: Adoption of CHC for nongynecologic cytology cases is worldwide, with 88.5% of institutions performing CHC on these specimens, a substantial increase from previous years. Performance of CHC varied by institution type, with clinic or regional/local independent laboratories and national/corporate laboratories performing CHC significantly less frequently than hospitals, university hospitals/academic medical centers, and Veterans Administration/Department of Defense hospital institutions. Most CHC was performed concurrently in real time, when the corresponding surgical specimen was reviewed. Selection for real-time concurrent CHC was by the interpreting pathologist, the pathologist diagnosing the surgical biopsy sample or cytopathology case, or both. Sampling was by far the most common reason for discordance. A 2-step difference was the most frequent threshold for discordance between cytology and surgical specimens, but this criterion varied among institutions, with no majority definition. The positive predictive value of a positive cytology finding was calculated rarely in North American institutions but was calculated more frequently in international institutions. Conclusions.--: CHC practices for nongynecologic cytopathology mirror those found for CHC of gynecologic cytopathology.